2017
DOI: 10.5455/njppp.2018.8.0936612102017
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations of serum electrolyte levels in iron deficiency anemia - A comparative analysis

Abstract: Background: Iron deficiency anemia (IDA) and electrolyte imbalance are widely prevalent problems in Indian population. Although few studies have linked IDA with altered serum electrolyte levels, their results were inconsistent. Since IDA is a major public health problem, the suggested relationship between the two assumes clinical importance. In IDA, red cell membrane-bound Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…Studies by Lavanya Rajagopal et al indicated that the mean PDW among uncontrolled diabetics was much higher than those with controlled diabetes and non-diabetics. [9] Ansari et al, Bhanukumar et al, Sharma et al, Biadgo B et al, Jabeen F et al, Kamilla et al also observed higher values of PDW in diabetic patients when compared to non-diabetics . These differences were found to be statistically significant.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Studies by Lavanya Rajagopal et al indicated that the mean PDW among uncontrolled diabetics was much higher than those with controlled diabetes and non-diabetics. [9] Ansari et al, Bhanukumar et al, Sharma et al, Biadgo B et al, Jabeen F et al, Kamilla et al also observed higher values of PDW in diabetic patients when compared to non-diabetics . These differences were found to be statistically significant.…”
Section: Discussionmentioning
confidence: 92%
“…A strong positive correlation was found between PDW and HbA1c levels. [ 3,8,9,10,13] Significant increases were observed with various grades of HbA1c levels. [9] PDW was significantly higher in the diabetics with HbA1c >7%, when compared to diabetics with HbA1C ≤ 7 %.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations